2020
DOI: 10.1186/s12889-020-8322-8
|View full text |Cite|
|
Sign up to set email alerts
|

Socioeconomic - related inequalities in overweight and obesity: findings from the PERSIAN cohort study

Abstract: Background: Overweight and obesity are major health concerns worldwide, with adverse health consequences during the life span. This study measured socioeconomic inequality in overweight and obesity among Iranian adults. Methods: Data were extracted from 129,257 Iranian adults (aged 35 years and older) participated in the Prospective Epidemiologic Research Studies in IrAN (PERSIAN) in 14 provinces of Iran in 2014. Socioeconomic-related inequality in overweight and obesity was estimated using the Concentration I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 54 publications
(54 reference statements)
3
25
1
1
Order By: Relevance
“…The wealth index was measured, using 15 items (including housing, car, washing machine, dishwasher, Freezer, computer, internet access, motorcycle, car rental, car type, vacuum cleaner,color TV, TV type, bathroom, cell phone) by principal component analysis (PCA) method then wealth index was categorized into five groups, from the poorest to the richest [15].…”
Section: Data Collection and Measurementmentioning
confidence: 99%
“…The wealth index was measured, using 15 items (including housing, car, washing machine, dishwasher, Freezer, computer, internet access, motorcycle, car rental, car type, vacuum cleaner,color TV, TV type, bathroom, cell phone) by principal component analysis (PCA) method then wealth index was categorized into five groups, from the poorest to the richest [15].…”
Section: Data Collection and Measurementmentioning
confidence: 99%
“…In the WHO's definition, high blood sugar plus two abovementioned factors are considered to be a metabolic syndrome [ 8 ]. Following strong evidence to support the role of central obesity as a major contributor to MetS and given the significant ethnic differences in the definition of obesity, the World Diabetes Federation set another set of diagnostic criteria for MetS to highlight the role of central obesity and ethnic differences that included obesity plus having two abovementioned factors [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have explored the relationship between SES (education and income in this study) and obesity, and evidence has shown that SES was strongly related to obesity in prospective cohort studies (29‐32). The framework of social determinants of health suggests that material, psychosocial, and behavioral factors contribute to the explanation of SES inequalities in obesity (33).…”
Section: Discussionmentioning
confidence: 99%